Evidence of multisensory plasticity: Asymmetrical medial geniculate body in people with one eye - Stefania S. Moro; Krista R. Kelly; Larissa McKetton; Brenda L. Gallie; Jennifer K.E. Steeves (NeuroImage: Clinical, 2015)
The medial geniculate body (MGB) plays a central role in auditory processing with both efferent and afferent tracts to primary auditory cortex. People who have lost one eye early in life have enhanced sound localization, lack visual over auditory dominance and integrate auditory and visual information optimally, similar to controls, despite taking longer to localize unimodal visual stimuli. Compared to controls, people with one eye have decreased lateral geniculate nuclei (LGN) volume as expected given the 50% deafferentation of the visual system. However, LGN volume is larger than predicted contralateral to the remaining eye, indicating altered structural development likely through recruitment of deafferented LGN cells. Purpose: the current study investigated whether structural MGB changes are also present in this group given the changes they exhibit in auditory processing. Methods: MGB volumes were measured in adults who had undergone early unilateral eye enucleation and were compared to binocularly intact controls. Results: unlike controls, people with one eye had a significant asymmetry with a larger left compared to right MGB, independent of eye of enucleation. MGB volume correlated positively with LGN volume in people with one eye. Conclusions: volume asymmetry in the MGB in people with one eye may represent increased interactions between the left MGB and primary auditory cortex. This interaction could contribute to increased auditory and other left hemisphere-dominant processing, including language, as compensation for the loss of one half of visual inputs early in life. The positive correlation between MGB and LGN volume is not due to space constraints but rather indicates increased plasticity in both auditory and visual sensory systems following early eye enucleation.